Comparison of proximal gastrectomy and total gastrectomy in proximal gastric cancer: a meta-analysis of postoperative health condition using the PGSAS-45 - Xiangyu Yang; Zhili Zeng; Ziyue Liao; Caiyu Zhu; Hongyang Wang; Haijuan Wu; Shu Cao; Weizheng Liang; Xiushen Li (BMC Cancer)
Abstract Purpose Proximal gastrectomy (PG) offers advantages over total gastrectomy (TG) in enhancing the postoperative nutritional status of patients with proximal gastric cancer (PGC), yet its effect on long-term quality of life is still debated. This study aims to thoroughly compare postoperative health condition outcomes between PG and TG. Methods We conducted a systematic search of English-language articles from the PubMed, Web of Science, and Cochrane Library databases, covering studies published up to February 2023. Key evaluation endpoints included surgical outcomes and postoperative health condition, assessed using the Post-Gastrectomy Syndrome Assessment Scale-45 (PGSAS-45). Results Six retrospective cohort studies were included in the analysis. The PG group demonstrated no significant negative impact on surgical outcomes compared to the TG group. Notably, patients who underwent PG experienced a superior postoperative health condition, characterized by fewer gastroesophageal reflux symptoms (WMD = -0.106, 95% CI -0.183 to -0.029, P < 0.01), less weight loss (WMD = 4.440, 95% CI 3.900 to 4.979, P < 0.01), and reduced dietary dissatisfaction (WMD = -0.205, 95% CI -0.385 to -0.025, P = 0.03). Conclusion This study provides compelling evidence that PG is superior to TG in enhancing postoperative health condition for patients with proximal gastric cancer, without compromising surgical outcomes. However, further rigorous randomized controlled trials are necessary to inform surgical decision-making more effectively.